1989
DOI: 10.1007/bf00015219
|View full text |Cite
|
Sign up to set email alerts
|

Contribution � la connaissance de la faune parasitaire d' Argentine, XV. Etude morphologique de Heteroxynema (Cavioxyura) viscaciae n. sp. (Nematoda, Heteroxynematidae) parasite de Lagidium viscacia boxi (Mammalia, Rodentia)

Abstract: R&urn6Heteroxynema (Cavioxyura) viscaciae n. sp., parasite du caecum et du gros intestin d' un rongeur caviomorphe d' Argentine, Lagidium viscacia boxiThomas, est dbcrit. Cette nouvelle espece est tres proche de Heteroxynema (Cavioxyura) chiliensis Quentin, 1975, parasite d' octodon degus (Molina) au Chili, dont elle se distingue essentiellement par ses mensurations et par la disposition de certaines papilles genitales des males. L' etude de cette nouvelle espbce montre l' existence: (i) au niveau des structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
1
10
0
2
Order By: Relevance
“…Based on the characteristics of the eggs of the parasites found in this study and on knowledge regarding the parasite fauna of modern viscachas, the faeces were ten- tatively attributed to L. viscacia (Caviomorpha: Chinchillidae) (Hugot & Sutton 1989, Denegri et al 2003.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on the characteristics of the eggs of the parasites found in this study and on knowledge regarding the parasite fauna of modern viscachas, the faeces were ten- tatively attributed to L. viscacia (Caviomorpha: Chinchillidae) (Hugot & Sutton 1989, Denegri et al 2003.…”
Section: Discussionmentioning
confidence: 91%
“…In Argentina, Teixeira de Freitas and Lins de Almeida (1936) ciae was described by Sutton and Hugot (1989) from L. viscaciae collected from Chubut Province. Foster et al (2002) and Ferreira et al (2007) confirmed the presence of this parasite in wild viscacha Lagostomus maximus from La Pampa and Chaco Provinces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the new genus differs from all these genera by the following main characteristics: Dermatopallarya have three lips and a defined buccal cavity instead of six lips and a mouth opening directly to the esophagus, as in the new genus; in addition, males of Dermatopallarya possess two ventral cuticular swellings, which are absent in the new genus (Petter & Quentin 1976, Skrjabin 1982; the esophageal bulb in Fastigiuris is reduced or absent whereas this structure is well developed in the new genus; also, the cervical alae in Fastigiuris are markedly bent in the ventral region (Petter & Quentin 1976) while the cervical alae are straight in the specimens described in this study. Likewise, Lamotheoxyuris can be differentiated from Heteroxynema because males of this later genus have a precloacal pseudosucker, gubernaculum, and a spicule (Petter & Quentin 1976, Hugot & Sutton 1989, which are all lacking in the new genus. Ivaschkinonema possesses four differentiated lips and caudal rings (Erkulov 1975), whereas Lamotheoxyuris has six lips and lacks caudal rings.…”
Section: Remarksmentioning
confidence: 99%
“…En Argentina, alrededor de cinco especies de Oxyuridae han sido encontradas en roedores (Sutton, 1978;Hugot y Sutton, 1989;Sutton y Hugot, 1993). Mientras que especies de Trichuridae y Capillariidae han sido halladas en humanos, aves y peces (Digiani, 1999;Carballo y Navone, 2007), pocas especies se han registrado en mamíferos y entre los roedores sólo puede mencionarse la presencia de una especie parásita en un sigmodontino de la tribu akodontini (Suriano y Navone, 1994;Navone et al, en prensa).…”
Section: Introductionunclassified